Feeding Guidance Methodology Aimed to Personnel Responsible of Food Management in a Mexican Nursery Program (P04-020-19) - Morales-Ruan, Carmen (Curr Dev Nutr, 2019)
OBJECTIVES: To enhance the knowledge of the personnel about correct feeding of girls and boys under six years old, that attend to a Mexican social program nurseries. METHODS: A methodology for feeding guidance (MFG) was pilot-tested and applied for personnel responsible of preschool children feeding from nurseries belonging to five different states from the country: Mexico City, Chihuahua, Jalisco, Morelos and Yucatán. MGF consisted in provide and replicate five thematic sessions with the same pedagogic structure which includes a video projection and conduction of individual as well as group activities aimed to information reinforcement and reflection. Sessions were given at three levels according to the personnel function in the nursery: 1) directors, supervisors and administrative personnel; 2) supervisors and responsible 3) responsible assistants and cooks. In order to evaluate the MGF efficacy knowledge questionnaires were applied before (pre-test) and after (post-test) the sessions. RESULTS: A total of 15 workshops with 328 participants were organized, a considerable increase was found in the mean and percentage of tests approved when comparing pre-test with posttest on every level of all the workshops, being the kitchen's personnel whom showed the greater rise in their knowledge. (25% more approved). CONCLUSIONS: MGF is an adequate strategy for providing guidance to the personnel involved in the feeding of beneficiaries of Mexican nurseries social program. FUNDING SOURCES: National System for the Integral Development of the Family.